Islamic Community of Pangudi Agama Sutji in Badean Village Bangsalsari Jember: Komunitas Islam Pangudi Agama Sutji di Desa Badean Bangsalsari Jember - Muhammad Arif Mustaqim (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the dynamic negotiation between Islamic practice and local Javanese tradition through a case study of the Pangudi Agama Sutji community in Badean Village, Indonesia, arguing that ritual transformation merits investigation because it illuminates how religious legitimacy and social cohesion are maintained amid modernization and generational change. Prior scholarship has addressedsyncretism and religious reform broadly but has paid limited attention to how local institutions actively mediate ritual continuity and change, leaving a gap in understanding institutional strategies that reconcile tradition with orthodoxizing pressures. The central research question asks how the Pangudi Agama Sutji community reconfigures the Birighen tradition to preserve communal functions while aligning with contemporary Islamic norms. The study focuses on Badean Village as the locus for an in-depth qualitative single-case inquiry. Data were obtained through participant observation, semi-structured interviews with religious leaders, elders, and youth, and documentary review, employing triangulation to enhance validity. Data analysis followed thematic and interpretive coding complemented by crosssource validation to trace negotiation processes. Findings reveal an adaptive, not erosive, transformation the community reframes ritual language, leadership roles, and pedagogic practices to retain solidarity and legitimacy. Novelty lies in evidencing institutional mediation as a mechanism of cultural resilience. Recommendations include participatory preservation policies and comparative or longitudinal research on education and social media’s role in ritual change.